ANALYZING THE PLACEMENT OF NEGATION MARKERS IN THE LAMNSO LANGUAGE - Nfor, J; Tanyi, E (Research Journal of Literature, Languages and Linguistics, 2024)
This paper investigates the syntactic presentation and distribution of negative markers in the Bantu language of Lamnso, with a focus on the negation particles yo' and la'. Using the Principles and Parameters Theory and analyzing the Lamnso tense system, the study reveals that yo' operates as a free morpheme generated below the TP and above the VP in all contexts of time-specifications (tenses) at the DStructure, while la' remains constantly generated below the TP within the Conditional Phrase (ConP). Negation is a grammatical phenomenon employing free morphemes, and in-situ generations involve no movement, while ex-situ generations involve a head transformational movement of yo' from NEG to AGR for certain tenses. The Split-Inf hypothesis of Pollock (1989) is used to explain the syntactic distribution of negation markers, which are generated above the TP within the NEGP node. The paper contributes to the understanding of negation in Lamnso and its structuring within Bantu languages, and presents a theoretical framework that can be applied to analyze negation in other languages